A modern farm house - Bayles, Julia Susanna (My University, 1907)
Introduction: There should exist a definite relation between the work of a housekeeper and that of the architect. In planning the house the architect should consider the work that is to be done, and so arrange and adjust the plan as to make these duties as light as possible for the prospective housekeeper. Primarily a house was a place in which to eat and sleep, but the present requirements suggest that we should not eat in the same room in which we cook, and that we should have light, well ventilated bedrooms apart from the rest of the house. Most of the household conveniences are modern. It is only within the past few years that they have come into consideration. In the large house the work is greatly increased unless these modern means are used to lighten the labor.
Citation: Bayles, Julia Susanna. A modern farm house. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Farm Houses; Architecture; Modern Housing; Theses